The Effect of Administrative Fine Regulation on the Korean Telecommunications Regulatory Accounting Regime - Hoon Jung; Bumjoon Kim; Sun A. Kang (International Telecommunications Society (ITS), 2024)
This research empirically investigates the effect of the administrative fine regulation on annual operating report within the Korean telecommunications regulatory accounting system.
Keywords: 330; Administrative Penalty; Administrative Fine; Telecommunications Regulatory Accounting; Accounting Separation